A consequence of invertibility on the normal form of a MIMO nonlinear systems. Issue 18 (2016) - Wang, Lei; Isidori, Alberto; Marconi, Lorenzo; Su, Hongye
Abstract: In this paper, a relevant consequence of invertibility on the normal form of MIMO nonlinear systems is presented. Making full use of the definition of uniform invertibility in the sense of Singh, the multipliers δ i +1 ( x )'s in the normal form are shown to possess a special property, that is to be triangularly dependent on the x 2, i 's. As a matter of fact, this property turns out to be necessary and sufficient for uniform invertibility in the case of a two-input two-output systems having normal form. Moreover, we also show that invertibility, or this special property of the multipliers, is a sufficient condition of uniform complete observability.